26th ACM Symposium on Virtual Reality Software and Technology 2020
DOI: 10.1145/3385956.3418956
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Projection Planes for the Visual Comparison of Photogrammetric 3D Reconstructions with Photo Footage

Abstract: Image-based 3D reconstructions and their visualization in virtual reality promise novel opportunities to explore and analyze 3D reconstructions of real objects, buildings and places. However, the faithfulness of the presented data is not always obvious and, in most cases, a 3D reconstruction cannot be compared directly to its corresponding real world instance. However, in case of reconstruction methods based on structure from motion (SFM), a large number of raw photos is available. This motivated us to develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Furthermore, with the continuous advancement of technology and application platforms, a plethora of design guidelines for virtual museums have emerged, covering various platforms such as Augmented Reality (AR) [44,48], Virtual Reality(VR) [49,50], Mixed Reality (MR) [51,52], and Extended Reality (XR) [53]. Within the domain of OVM, Lin et al identified four critical design features (usability, aesthetics, sensory appeal, personalization) and five guidelines (interactivity, content relevance, ease of use, emotional engagement, discovery) [54].…”
Section: Virtual Museum Navigation Experiencementioning
confidence: 99%
“…Furthermore, with the continuous advancement of technology and application platforms, a plethora of design guidelines for virtual museums have emerged, covering various platforms such as Augmented Reality (AR) [44,48], Virtual Reality(VR) [49,50], Mixed Reality (MR) [51,52], and Extended Reality (XR) [53]. Within the domain of OVM, Lin et al identified four critical design features (usability, aesthetics, sensory appeal, personalization) and five guidelines (interactivity, content relevance, ease of use, emotional engagement, discovery) [54].…”
Section: Virtual Museum Navigation Experiencementioning
confidence: 99%
“…For multiple object selection, researchers have also developed techniques that map the position of users' hands to virtual brushes and lassos [164]. Translation 18 [3, 41-43, 73, 86, 91, 100, 108, 116, 125, 159, 185, 187, 191, 192, 195, 199] Scaling 27 [3, 9, 28, 33, 38, 41-43, 83, 86, 89, 91, 104-106, 120, 121, 159, 161, 170, 185-187, 191, 199, 204, 207] Duplication 18 [7,32,49,89,99,103,106,112,120,121,138,167,180,188,204,204,207,209] Body 55…”
Section: Bodymentioning
confidence: 99%